2019
DOI: 10.1186/s41747-019-0120-7
|View full text |Cite
|
Sign up to set email alerts
|

Fully automated convolutional neural network-based affine algorithm improves liver registration and lesion co-localization on hepatobiliary phase T1-weighted MR images

Abstract: BackgroundLiver alignment between series/exams is challenged by dynamic morphology or variability in patient positioning or motion. Image registration can improve image interpretation and lesion co-localization. We assessed the performance of a convolutional neural network algorithm to register cross-sectional liver imaging series and compared its performance to manual image registration.MethodsThree hundred fourteen patients, including internal and external datasets, who underwent gadoxetate disodium-enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Research by Jiang et al 32 showed that 4-dimensional computed tomography (CT) deformed image registration of the lung based on CNN had the smallest error compared with various traditional methods, and the registration time was 1.4s. Hasenstab et al 33 evaluated the performance of a CNN algorithm for liver registration in 314 patients, and compared it with manual image registration. The results showed that compared with manual registration, the liver overlap and image correlation for automatic registration were higher.…”
Section: Methodsmentioning
confidence: 99%
“…Research by Jiang et al 32 showed that 4-dimensional computed tomography (CT) deformed image registration of the lung based on CNN had the smallest error compared with various traditional methods, and the registration time was 1.4s. Hasenstab et al 33 evaluated the performance of a CNN algorithm for liver registration in 314 patients, and compared it with manual image registration. The results showed that compared with manual registration, the liver overlap and image correlation for automatic registration were higher.…”
Section: Methodsmentioning
confidence: 99%
“…The problem is that the regularizer terms like L2-norm cannot be applied to the affine transformation with such an encrypted set of parameters. Actually, the regularizer can only be applied to the transformation fields as reported by the related works (Hasenstab et al, 2019), (Lee et al, 2019), and (Boveiri et al, 2021).…”
Section: Nomentioning
confidence: 99%
“…There is great interest in applying artificial intelligence to improve MRI image quality, image registration, and workflow [73,[82][83][84] all of which are active areas of investigation.…”
Section: Future Direction: Meeting Challenges Of Mri With New Technologymentioning
confidence: 99%